British Romanticism in European Perspective Into the Eurozone - Clark, Steve; Connolly, Tristanne; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
What, and when, is British Romanticism, if seen not in island isolation but cosmopolitan integration with European Romantic literature, history and culture? The essays here range from poetry and the novel to science writing, philosophy, visual art, opera and melodrama; from France and Germany to Italy and Bosnia.
Keywords: European literature; Literature—Philosophy.; Culture—Study and teaching; British literature; Literature, Modern—19th century; Literature—History and criticism; European Literature; Literary Theory; Cultural Theory; British and Irish Literature; Nineteenth-Century Literature; Literary History